An annotated checklist of the mantis shrimps of India (Crustacea: Stomatopoda) - Trivedi, Jigneshkumar N.; Ahyong, Shane T.; Vachhrajani, Kauesh D.; Kumar, Appukuttannair Biju (Zootaxa, 2020)
An annotated checklist of the mantis shrimps (Stomatopoda) occurring in India is compiled from published literature and specimens collected from coastal areas of Gujarat state. A total of 72 species, 35 genera, 10 families and 5 superfamilies reported from Indian waters are listed. Four species were recorded for the first time from Gujarat while one species, Erugosquilla hesperia (Manning, 1968), is confirmed for the first time from India. The maximum number of species was reported from Tamil Nadu (48 species), while fewest species were reported from Karnataka (2 species). The results also suggest that the east coast is more diverse (66 species) than the west coast of India (32 species).